2022
DOI: 10.3390/ijerph19084484
|View full text |Cite
|
Sign up to set email alerts
|

Eating Competence, Food Consumption and Health Outcomes: An Overview

Abstract: Eating Competence (EC) is one behavioral perspective of eating practices that has been associated with a healthy lifestyle. It emphasizes eating pleasure, self-regulation of eating, body weight satisfaction, and regular meal frequency that includes food variety without focusing on dietary guidelines. EC is composed of four components (Eating Attitude, Food Acceptance, Internal Regulation, and Contextual Skill), and its assessment is performed using the Eating Competence Satter Inventory (ecSI2.0™), developed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 64 publications
2
16
0
Order By: Relevance
“…Our study showed that among individuals with GRDs, EC is directly associated with schooling, income, cooking skills, following a non-conforming GFD, and having a good food acceptance. These results are in line with previous studies where EC was associated with socioeconomic data [ 15 , 26 , 36 , 40 , 42 , 44 , 77 , 78 , 79 , 80 ]. Another important result in this study was the overall percentage of competent eaters (56.1%), showing that people with some GRDs tend to be more concerned about their diet.…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed that among individuals with GRDs, EC is directly associated with schooling, income, cooking skills, following a non-conforming GFD, and having a good food acceptance. These results are in line with previous studies where EC was associated with socioeconomic data [ 15 , 26 , 36 , 40 , 42 , 44 , 77 , 78 , 79 , 80 ]. Another important result in this study was the overall percentage of competent eaters (56.1%), showing that people with some GRDs tend to be more concerned about their diet.…”
Section: Discussionsupporting
confidence: 93%
“…Among these are the potential nutritional deficits, increased risk of hypoglycemia, and various psychological effects that impact eating behavior, such as feelings of guilt, shame, or social isolation [ 24 ]. Both emotional and behavioral manifestations influence how individuals eat [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eating competence may still be developing and/or disrupted during college years when young adults experience greater autonomy from parents and/or caregivers, instability of relationships, and shifts in social roles ( Auerbach et al, 2018 ); and many college students may be newly responsible for managing their own food. ecSatter is an encompassing model that provides an ideal framework in which to study eating behaviors of college students: It addresses the skills and resources necessary for managing the food environment to provide reliable and regular eating opportunities that, in turn, support dietary variety and internal cues and processes for regulating food intake ( de Queiroz et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%